ظاهرة الفقر في العراق : الواقع والمعالجات ( للمدة 1976- 2006) (المجلة العراقية للعلوم الاقتصادية, 2018)
Poverty is a complex concept that includes economic, social, political, cultural and environmental dimensions; it’s a situation of deprivation that reflected in the consumption of less food and low level of health and achievements of education, also poor housing conditions and a shortage of financial assets, capital and savings. All of these factors make the individual or family have a severe sensitivity to changes and foreign shocks. Many attempts was developed at the beginning of the last decade of the last century - with the increased attention to human development - the defining, investigating and measuring of poverty. The goal of this research is to clarify the theoretical concepts on the one hand, and try to survey the status of poverty and the poor in Iraq on the other hand; leading to better economic policies can limit the phenomenon of poverty